2017
DOI: 10.1073/pnas.1706080114
|View full text |Cite
|
Sign up to set email alerts
|

Climate-driven changes in functional biogeography of Arctic marine fish communities

Abstract: SignificanceArctic marine ecosystems are experiencing a rapid biogeographic change following the highest warming rates observed around the globe in recent decades. Currently, there are no studies of how the observed shifts in species composition are affecting Arctic marine ecosystem functioning at a biogeographic scale. We address this issue via functional biogeography and show that increasing temperatures and reduced ice coverage are associated with the borealization of Arctic fish communities. We find that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
189
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(232 citation statements)
references
References 69 publications
11
189
2
Order By: Relevance
“…Grid cells along the West Greenland continental shelf have been masked due to a lower number of tagging locations in these areas than in Canadian waters resulting in less confidence in identifying hotspots and coldspots The most pervasive threat to the Arctic and its wildlife is climate change, where decreases in the body condition of marine mammals and seabirds (Harwood, Smith, George, et al, 2015;Sciullo, Thiemann, & Lunn, 2016) have been observed in association with changing sea ice conditions. A warming Arctic is redistributing species with more temperate-associated species expanding their range northwards, which has changed the trophic structure of the Arctic ecosystem Frainer et al, 2017;Kortsch, Primicerio, Fossheim, Dolgov, & Aschan, 2015;Yurkowski et al, 2017). Furthermore, interest in expanding fisheries exploitation of coastal and offshore waters within EEZs of Arctic nations is high (Christiansen, Mecklenburg, & Karamushko, 2014), which can increase risks of entanglement and bycatch mortality, a global cumulative threat to marine megafauna (Lewison et al, 2014) that can lead to trophic downgrading (Estes et al, 2011).…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…Grid cells along the West Greenland continental shelf have been masked due to a lower number of tagging locations in these areas than in Canadian waters resulting in less confidence in identifying hotspots and coldspots The most pervasive threat to the Arctic and its wildlife is climate change, where decreases in the body condition of marine mammals and seabirds (Harwood, Smith, George, et al, 2015;Sciullo, Thiemann, & Lunn, 2016) have been observed in association with changing sea ice conditions. A warming Arctic is redistributing species with more temperate-associated species expanding their range northwards, which has changed the trophic structure of the Arctic ecosystem Frainer et al, 2017;Kortsch, Primicerio, Fossheim, Dolgov, & Aschan, 2015;Yurkowski et al, 2017). Furthermore, interest in expanding fisheries exploitation of coastal and offshore waters within EEZs of Arctic nations is high (Christiansen, Mecklenburg, & Karamushko, 2014), which can increase risks of entanglement and bycatch mortality, a global cumulative threat to marine megafauna (Lewison et al, 2014) that can lead to trophic downgrading (Estes et al, 2011).…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…Evaluating the spatial and temporal dynamics of fish communities is crucial for understanding and predicting the impacts of global environmental change on marine ecosystem functioning and services (Frainer et al, ; Givan, Edelist, Sonin, & Belmaker, ; Holmlund & Hammer, ; Worm et al, ). Fishes are the dominant vertebrates in marine food webs and strongly influence ecosystem processes such as nutrient cycling, carbon storage, water quality and habitat maintenance (Allgeier, Burkepile, & Layman, ; Bascompte, Melián, & Sala, ; Holmlund & Hammer, ; Villéger, Brosse, Mouchet, Mouillot, & Vanni, ).…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of biodiversity through such global change will demand biogeographic shifts at all levels of biological organization (e.g. from populations to communities to functional groups, Bhatta, Grytnes, & Vetaas, ; Frainer et al, ; McLachlan, Hellmann, & Schwartz, , respectively. See also Barnosky et al, , for a recent review).…”
Section: Introductionmentioning
confidence: 99%